Enhancing Strength and Durability of Cement Concrete Using Metakaolin, Waste Glass, and Glass Fibres - Yashpal Kumar; Bajpai, Rishabh (Cuestiones de Fisioterapia, 2025)
Enhancing cement concrete's strength and durability is crucial for sustainable infrastructuredevelopment. This study investigates the effects of metakaolin (MK) and waste glass (WG) as partialcement and sand replacements, respectively, along with glass fibers (GF) on the mechanical propertiesof concrete. Five mix designs (S1–S5) were developed with varying metakaolin content (2%, 4%, 6%,8%, and 10% of cement weight), maintaining a constant 0.50% GF and optimized WG replacement.Compressive strength tests at 7, 28, and 91 days revealed a consistent improvement with increasingMK content, with S5 (10% MK) exhibiting the highest compressive strength (21.27 MPa at 7 days,28.57 MPa at 28 days, and 29.81 MPa at 91 days). Split tensile strength results followed a similartrend, with S5 achieving the maximum values across all curing periods